EFFECT OF PORT SITE BUPIVACAINE INFILTRATION ON POST OPERATIVEPARENTRAL ANALGESIC REQUIREMENT IN EARLY POST OPERATIVE PERIOD AFTER LAPAROSCOPIC CHOLECYSTECTOMY - Muhammad Rehman Gulzar; Umer Farooq; Muhammad Akram (Journal of University Medical & Dental College, 2019)
ABSTRACT: BACKGROUND: Post Cholecystectomy pain is a very important factor aﬀecting administration of analgesics, delayed oral intake and making decisions of discharge while intensity of pain is relevant [1,18]to patient distress. OBJECTIVE: To observe the eﬀect of port- site Bupivacaine inﬁltration on post operative parentral analgesic requirement in patients undergoing Laparoscopic cholecystectomy. MATERIAL AND METHODS: A total of 100 cases were included in this study and were admitted through OPD for elective laparoscopic cholecyctectomy . They were divided in to two groups. Group A (study group) received 10 mL of 0.25% bupivacaine injection in 4 ports ; 7 mL in epigastric and umbilical ports , 3 mL in the other two port sites at the end of surgery.Group B (control Group) received no Local analgesic treatment. Post operative monitoring and pain assessment was done using Wong Baker FACES pain rating scale. Inj Toradol (NSAID) 30 mg intravenous was given as recue analgesic when pain rating scale >3 was observed within 24 hours. RESULTS: Post operative pain was reduced as a result of bupivacaine inﬁltration in Group A as compared to Group B.Mean abdominal pain score was maximum at 6 hours in Group A with the stv alue of 3.5 and minimum at 1 hour value 1.7. While at 3 hours in Group B Maximum score was seen at 5.1. Group A had a lower incidence of shoulder pain in comparison with the control group although statistically not signiﬁcant. CONCLUSION: Portsite inﬁltration of bupivacaine signiﬁcantly reduces the post chlecystectomy discomfort and pain.